Repurposing Antispasmodic Agent Otilonium Bromide for Treatment of Staphylococcus aureus Infections - Zhou, Linying; She, Pengfei; Tan, Fang; Li, Shijia; Zeng, Xianghai; Chen, Lihua; Luo, Zhen; Wu, Yong (Frontiers in Microbiology, 2020)
Recently, the problem of bacterial resistance has been brought into focus, which makes the development of new antibiotics become a necessity. Compared with traditional development approaches, drug repurposing provides a faster and more effective approach to find new antimicrobial agents. In this study, we found that antispasmodic agent otilonium bromide had strong antibacterial ability and bactericidal activity against Staphylococcus aureus, with MICs of 4 to 8 µg/ml, and bacteria could be killed completely after treatment with 2MIC of OB for 5h. Furthermore, it had a potent effect on eradicating biofilm at concentrations ranging from 16 to 64µg/ml. At the same time, it had low tendency to develop resistance and possessed limited cytotoxicity. In MRSA-infected mouse peritonitis model, it was also effective to cure mice and improve their survival rate. Additionally, we observed that otilonium bromide changed the permeability of bacterial membrane and caused membrane damage, and it is probably the antibacterial mechanism of otilonium bromide. Taken together, our results indicated that otilonium bromide could be a new antimicrobial agent to treat Staphylococcus aureus infections more safely and efficiently.